Cluster and Location Based Overlay Multicast in Mobile Ad Hoc and Sensor Networks - Hyung-Ok Lee; Ji-Seung Nam; Jin-Han Jeon (International Journal of Distributed Sensor Networks, 2014)
We propose a novel overlay multicast protocol over wireless sensor network, CLOM (cluster and location based overlay multicast) which use both cluster based approach and location based approach. A cluster based approach is used to manage multicast group consisting of relatively large number of nodes while a location based approach is used to construct a multicast tree with rapidity and low control overhead by using geometric information taken from GPS device. Additionally, the information of damping area and the scheme for reducing the CH node discovery time and control overhead have been introduced into CLOM to improve the performance of the tree. The simulation results showed that CLOM works properly with low data distribution delay and low control overhead where the number of multicast group members is relatively high.